Quota restrictions and intra-firm reallocations: evidence from Chinese exports to the US - Upward, Richard; Wang, Zheng (Elsevier, 2016)
We study how Chinese textile and clothing firms adjusted the product structure of their exports to the US, as triggered by the termination of Multifiber Arrangement (MFA) quotas. We find that the removal of MFA quotas induced firms to expand their product scope while reducing the concentration on their core product. These effects are strong for domestic and foreign privately-owned firms, but insignificant for state-owned firms.